The Effect of Home Heart Walk on Fatigue among Heart Failure’s Patients - Yanti Anggraini Aritonang; Ni Luh Widani; Irene Adyatmaka (Faculty of Nursing Universitas Padjadjaran, 2018)
AbstractHeart failure is a physiologic state in which the heart cannot pump enough blood to meet the metabolic needs of the body. Fatigue is a major problem that arises in heart failure patients. One intervention to reduce fatigue is Home Heart Walk (HHW). The aim of this research was to determine the effect of HHW on fatigue among heart failure’s patients. This research used Pretest-Postest Design Pre-experiment design, at RSUPN Dr Cipto Mangunkusumo & RS PGI Cikini during May-July 2015, involving 50 heart failure patients with functional class 2 & 3.The nurse teached HHW to heart failure patients with a six-minute walking procedure with five meter’s distance in the hospital and then the exercise is continued at home within two days for six weeks. The result obtained majority of the respondents is clasification heart failure’s functional class two (76%). Before & after HHW’s intervention, the majority of normal pulse rate from 90% become 100%.The test results showed there was significant difference in the degree of fatigue before and after HHW‘s intervention (p=0.000) and there is a relationship between respiratory rate on the degree of fatigue (p=0.043). The conclusion is HHW can reduce fatigue in heart failure patients during six weeks. Therefore it is recommended for nurses to teach HHW and motivate patient to have self-exercise.